Women moving and expressions in doing living-Cerrado: Women moving and expressions in doing living-Cerrado (Élisée - Revista de Geografia da UEG, 2020)
Abstract: With this writing we want to think of the Brazilian Cerrado from the movements and expressions of different women. To this end, we carried out a methodological journey that involved extensive field research and interviews - in the Cerrado of Goiás and in transition with the Amazon - among quilombola, indigenous, coconut breakers, weavers, and cotton spinners women. We also used the experiences of the I Encontro Nacional das Mulheres do Cerrado, in 2019, where a letter written to hundreds of hands established that “the Brazilian Cerrado has the face of a woman”. The diversity, timeliness, and struggle of these women, manifested in the text, gave us guidelines for articulating the adjective cerradeira and the term living-Cerrado in our search for a more dignified life. These two expressions, cerradeira and living-Cerrado, are triggered throughout this article as a way of conceptualizing the broad processes of interaction between humans and non-humans from an environment that builds and is built at the same time by the biome, by culture and by socio-politics. At this point in the research, we conclude that the so-called ecofeminism, the theoretical perspective of amefricanity and other movements that denounce hierarchies and violence, are good leads to bring about changes. We add, however, that the living-Cerrado is in the plurality, ancestry and intergenerational and interspecific commitments that mark the cerradeira women.Keywords: Women. Living-Cerrado. Movement. Expressions.
Keywords: Women. Living-Cerrado. Movement. Expressions.